(untitled) (Journal of Informatics and Mathematical Sciences, 2010)
Consideration of a function shaping the surface of a solid of revolution as a random variable allows for extension of the proof that the disks and the shells methods give the same result from monotonic continuous functions to a subclass of Riemann-integrable functions.